Holographic Manipulation of Nanostructured Fiber Optics Enables Spatially‐Resolved, Reconfigurable Optical Control of Plasmonic Local Field Enhancement and SERS (Small 23/2022). Issue 23 (9th June 2022) - Collard, Liam; Pisano, Filippo; Zheng, Di; Balena, Antonio; Kashif, Muhammad Fayyaz; Pisanello, Marco; D'Orazio, Antonella; de la Prida, Liset M; Ciracì, Cristian; Grande, Marco; De Vittorio, Massimo; Pisanello, Ferruccio
Abstract : Plasmonics In article number 2200975, Liam Collard, Massimo De Vittorio, Ferruccio Pisanello, and co‐workers use wavefront engineering to harness the resonant properties of plasmonic nanostructures on the tip of a multimode fiber and spotlight specific resonances across the dispersion diagram to enable spatially‐resolved surface enhanced Raman spectroscopy and reconfigurable beam steering. [Cover image: artwork by Filippo Pisano].